Muscle microcirculation alterations and relation to dipping status in newly diagnosed untreated patients with arterial hypertension—A pilot study. (7th October 2017) - Tzanis, Georgios; Dimopoulos, Stavros; Manetos, Chris; Koroboki, Eleni; Manios, Efstathios; Vasileiadis, Ioannis; Zakopoulos, Nikolaos; Nanas, Serafim
Abstract: Objective: The importance of abnormalities observed in the microcirculation of patients with arterial hypertension (AH) is being increasingly recognized. The authors aimed to evaluate skeletal muscle microcirculation in untreated, newly diagnosed hypertensive patients with NIRS, a noninvasive method that evaluates microcirculation. Methods: We evaluated 34 subjects, 17 patients with AH (13 males, 49±13 years, BMI: 26±2 kg/m 2 ) and 17 healthy controls (12 males, 49±15 years, BMI: 25±3 kg/m 2 ). The thenar muscle StO2 (%) was measured by NIRS before, during and after 3‐minutes vascular occlusion to calculate OCR (%/min), EF (%/min), and RHT (minute). The dipping status of hypertensive patients was assessed. Results: The RHT differed between AH patients and healthy subjects (2.6±0.3 vs 2.1±0.3 minutes, P <.001). Dippers had higher EF than nondippers (939±280 vs 710±164%/min, P =.05). Conclusions: The study suggests an impaired muscle microcirculation in newly diagnosed, untreated AH patients.